(untitled) (World Bulletin of Education and Learning, 2025)
This study explores the interrelationship between logical thinking and didactic thinking within the educational process, focusing on their pedagogical significance in teacher education. In contemporary pedagogy, the effectiveness of teaching is increasingly associated with teachers’ ability to think logically, structure content coherently, and apply didactic reasoning in accordance with learners’ cognitive characteristics. Logical thinking is understood as the capacity to analyze, compare, generalize, and draw reasoned conclusions, while didactic thinking is viewed as a professional form of pedagogical reasoning that enables teachers to transform subject knowledge into accessible and meaningful learning content. The study emphasizes that these two forms of thinking are not isolated but function in close interdependence, jointly determining the quality of instructional design, classroom interaction, and learning outcomes. Special attention is given to the role of this interrelationship in higher pedagogical education, where future teachers are prepared to manage complex educational tasks and foster students’ intellectual development. The findings highlight that the integration of logical and didactic thinking contributes to more effective lesson planning, clearer explanation of concepts, and the creation of learner-centered educational environments. The study concludes that strengthening the interconnection between logical and didactic thinking is a key condition for improving the quality of pedagogical training and educational practice.